Chitosan-Honey Biomembrane Contributes to the Healing Process of Burn Wound in Male White Rats - Muslim Suardi; Wahyu Margi Sidoretno; Refika Sukriyani (Jurnal Ilmu Kesehatan Abdurrab, 2024)
Chitosan and honey posses antibacterial activity. The research objectives were to prepare chitosan and chitosan honey biomembrane, and evaluate the influence of chitosan and chitosan-honey-PVA biomembrane on burn wound healing in male white rats. The skin irritation was tested on five healthy volunteers. Twenty-four rats were divided into four groups. Burns were induced on the dorsal skin using a 2-cm-diameter metal plate at 80-100 oC for 5 seconds. The burn area was measured on days 3, 5, and 7 after injury. New blood vessels and bullae were observed histopathologically in scar tissue. Irritation was tested on five healthy volunteers. Bullae were observed in 5, 5, 5, 1, and 3 rats in the negative control, chitosan biomembrane, chitosan-honey biomembrane, and positive control (Sterile Amnion Lyophilized) groups, respectively. The wound area on day 5 after treatment was 3.06 ± 0.088, 2.29 ± 0.176, 2.64 ± 0.147, and 2.43 ± 0.201 cm2 for the negative control, positive control, chitosan-PVA biomembrane, and chitosan-honey-PVA biomembrane groups, respectively. No significant difference was found between the positive control and chitosan-honey-PVA biomembrane (p > 0.05). Chitosan-honey-PVA biomembrane contributes to the healing process of burn wounds.